Regionalne zróżnicowanie absorpcji funduszy Unii Europejskiej na inwestycje w gospodarstwach rolnych - Miś, Teresa (Regional Diversification in Absorption of EU Funds for Investment in Farms, 2009)
The paper undertakes an assessment of the participation of farmers in the absorption of EU funds for new investments in farms in regional frames. The study shows that regional diversification of agriculture in Poland translates into different possibilities of absorption of EU funding available for new investments in farms by farmers. Macro-regions, which have agriculture with a higher economic potential and more favorable agrarian structure, utilize assistance of the EU to higher degree than macro-regions, which have agriculture with a weak economic potential and a small-farm structure. It applies in particular to agriculture of south-eastern Poland, which, because of structural restrictions, its low profitability and other restrictions, is unable to fully utilize the financial assistance available for farmers, despite farmers' activity in those respects. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 750-759